Equity valuation : Rolls-Royce PLC - Fonseca, Mafalda Filipa Sousa (2014)
The purpose of this thesis is to evaluate Rolls-Royce PLC. In order to do so, two valuation methodologies will be presented. The first one regards the Discount Cash Flow – WACC methodology, where each sector of the company is valued. By doing so, it is possible to reach a price per share of 1369 pence. Therefore, when using this methodology, the company is presented as a buying opportunity (the market yields a price of 1112 pence.) The second valuation presented and which is introduced as a second stage valuation is the multiples one. By using the price to earnings ratio, it is possible to value RR at 988 pence. With this methodology, the company is presented as a selling opportunity. Finally, when comparing the valuation introduced in this thesis to the one performed by J.P.Morgan, it is possible to conclude that this valuation is more conservative than the one presented by the investment bank (J.P.Morgan presents a price of 1420 pence). The differences in the assumptions will be further analyzed in this report.